Hubungan Mutu Pelayanan dengan Minat Kunjung Pasien Rawat Jalan di RSU Hidayah Deli Tua - Melinda, Rima; Meliala, Sri Agustina (Universitas Malahayati, 2023)
ABSTRACT The quality of health services is something that can satisfy every user of health services in accordance with the level of satisfaction of the average population and the implementation is in accordance with standards. Interest in visiting is a behavior that appears as an object response that shows the customer's desire to make a repeat purchase. Based on the results of interviews and observations made with 10 patients who were being treated at Hidayah Hospital Deli Tua, 4 of them were interested in making a revisit, 6 others stated that they were not interested in making a revisit. This study aimed to determine the relationship between service quality and interest in outpatients visit at Hidayah Hospital Deli Tua. This is a quantitative using a cross sectional approach. The research was conducted at Hidayah Hospital Deli Tua. The study population was all old outpatients who were undergoing treatment at the Hospital and the sample was 98 people. Showed that tangible variables (physical evidence) had a p-value of 0.001 <0.05, reliability p-value 0.001 <0.05, responsiveness p-value 0.000 <0.05, assurance) p-value 0.000 <0.05, empathy p-value 0.000 <0.05. shows that there is a tangible relationship, reliability, responsiveness, assurance, empathy with the interest in outpatients visit. It is suggested to the Hospital to always pay attention and maintain the quality of service both in terms of facilities, infrastructure, time, cleanliness, and patient comfort by providing facilities to get services to increase interest in patient visits. Keywords: Quality of Service, Interest of Outpatients Visit ABSTRAK Mutu pelayanan kesehatan adalah pelayanan kesehatan yang dapat memuaskan setiap pemakai jasa pelayanan kesehatan yang sesuai dengan tingkat kepuasan rata-rata penduduk serta penyelenggaraanya sesuai dengan standar. Minat kunjung merupakan perilaku yang muncul sebagai respon objek yang menunjukkan keinginan pelanggan untuk melakukan pembelian ulang. Berdasarkan hasil wawancara dan observasi yang dilakukan kepada 10 pasien saat berobat ke Rumah Sakit Umum Hidayah Deli Tua, 4 orang diantaranya berminat melakukan kunjungan ulang. 6 orang lainnya menyatakan tidak berminat melakukan kunjungan ulang. Penelitian ini bertujuan untuk mengetahui hubungan mutu pelayanan dengan minat kunjung pasien rawat jalan di Rumah Sakit Umum Hidayah Deli Tua. Jenis penelitian yang digunakan kuantitatif dengan menggunakan pendekatan Cross Sectional. Lokasi penelitian di RSU Hidayah Deli Tua. Populasi penelitian seluruh pasien lama rawat jalan yang melakukan pengobatan di Rumah Sakit Umum Hidayah Deli Tua dan sampel sebanyak 98 orang. Hasil penelitian menunjukkan variabel tangible (bukti fisik) memiliki nilai p-value 0,001 < 0,05, reliability (reliabilitas) p- value 0,001 < 0,05, responsiveness (daya tanggap) p-value 0,000 < 0,05, assurance (jaminan) p-value 0,000 < 0,05, emphaty (empati) p-value 0,000 < 0,05. Kesimpulan ada hubungan tangible (bukti fisik), reliability (reliabilitas), responsiveness (daya tanggap), assurance (jaminan), emphaty (empati) dengan minat kunjung pasien rawat jalan. Saran yang diberikan adalah agar selalu memperhatikan dan tetap menjaga kualitas pelayanan baik dari segi sarana, prasarana, waktu, kebersihan, dan kenyamanan pasien dengan memberikan fasilitas untuk mendapatkan pelayanan sehingga dapat meningkatkan minat kunjung pasien. Kata Kunci: Mutu Pelayanan, Minat Kunjung Pasien Rawat Jalan